The effect of deposit insurance on market discipline: Evidence from a natural experiment on deposit flows - Alexei Karas; William Pyle; Koen Schoors (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
We explore how the introduction of explicit deposit insurance affects deposit flows into and out of banks of varying risk levels. Using evidence from a natural experiment in Russia, we employ a difference-in-difference estimator to isolate the change in the deposit flows of a newly insured group (households) relative to an uninsured control group (firms). This approach improves on earlier studies seeking to identify the effect of deposit insurance on market discipline. We find that the relative sensitivity of households to bank capitalization diminished markedly with the introduction of an insurance program covering their deposits. This was not true for firms, however. We then show the finding is not an artifact of the two groups responding differently to a minor banking crisis that arose at roughly the same time.
URN:NBN:fi:bof-201408072007
Keywords: 330